Unauthorised substances in food suplements - example of minerals - Amidžić, Maja; Banović Fuentes, Jelena; Mikulić, Mira; Torović, Ljilja (Archives of Pharmacy, 2022)
As the popularity and the number of food supplements on the market unprecedentedly rise, a plethora of associated risks to public health inevitably follows. A crucial element of a food safety system is rapid flow of information, in Europe operating through Rapid Alert System for Food and Feed (RASFF). RASFF historic records provide a tremendous database of countless food hazards. Accordingly, RASFF database was automatically searched using following criteria: food category “food supplements”, hazard category “composition”, period of assessment 2011-2021. Data related to selected classes of substances, including minerals and minerals' sources, were manually extracted and evaluated in terms of compliance with regulation establishing minerals and minerals' sources that may be used in manufacture of dietary supplements. Records showed tens of notifications, and their annual distribution showed the sharp maximum in 2014, with over 30 notifications. Non-compliances were evenly distributed among Mg, Cu, Zn, Cr, Mn, Mo, Se, B and V, while Ca, K and Fe were much less represented. It is noteworthy that for a substantial number of supplements multiple non-compliances were recorded, meaning simultaneous presence of several unauthorized sources of minerals. Analysis of background data indicated the most probable cause of such a high number of notifications – absolutely predominant were supplements originating from the United States of America, whereas European countries appeared only sporadically. Not taking into account regulatory differences between producing and selling countries leads to illicit practice of using unauthorized substances in dietary supplements, which need to be resolved in the best interest of consumers.